2000
DOI: 10.1080/09523980050184736
|View full text |Cite
|
Sign up to set email alerts
|

Students' Perceived Value of Video in a Multimedia Language Course

Abstract: AbstractsThis paper reports on a study of the use of video by learners in a multimedia language course, their perceptions of the contribution of video to learning and the affective evaluations they ascribe to video vs print sources. The subjects for the study were tertiary learners of Spanish enrolled in the rst semester of a distance learning programme. Data was gathered relating to students' choices of when and how to use video, how they represented video in the development of language skills, and affective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…For instance, this study found that ESL learning is much easier if commercial is comedic because it keeps students' interests and attention when people are making jokes even if they are not interested in the product, but makes them to smile at the joke and think of what they were saying. According White (2000) students prefer in engaging in video material rather than texts because the language is brought alive to contribute to a positive orientation to the language.…”
Section: Entertainment and Humormentioning
confidence: 99%
“…For instance, this study found that ESL learning is much easier if commercial is comedic because it keeps students' interests and attention when people are making jokes even if they are not interested in the product, but makes them to smile at the joke and think of what they were saying. According White (2000) students prefer in engaging in video material rather than texts because the language is brought alive to contribute to a positive orientation to the language.…”
Section: Entertainment and Humormentioning
confidence: 99%
“…One of these relates to the way in which video stimulates concentration and motivation in students throughout the teaching process (e.g., Roskos-Ewoldsen & Roskos-Ewoldsen 2001;Hazen, Kelly, & Sramek, 2002;Hoover, 2006;Oishi, 2007). The second area of benefit has to do with the power of video in helping students conceptualize and internalize difficult and abstract topics (e.g., Verran, 1992;Harwood & McMahon 1997;Liedtka 2001;Herron, Dubreil, Corrie, & Cole, 2002;Green, Voegeli, Harrison, Phillips, Knowles, Weaver, & Shephard, 2003; Brunvand & Fishman, 2007;De Leng, Dolmans, Van de Wiel, Muijtjens, & Van Der Vleuten, 2007;Palmer, 2007;White, 2007).…”
Section: Research Themes Referencementioning
confidence: 99%
“…Video viewing can enhance understanding of concepts that are intricate to verbally explain (White, Easton, & Anderson, 2000). Video with its visual and animated features can be a powerful addition to second language acquisition.…”
Section: Computer-based Video Instructionmentioning
confidence: 99%